2018
DOI: 10.3390/app8071203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Droplet Impingement on the Weld Profile and Grain Morphology in the Welding of Aluminum Alloys

Abstract: To achieve a better understanding of the effect of droplet impingement on the weld profile and grain morphology, welding with vertical and inclined torches in the double pulsed-gas metal arc welding of aluminum alloy were compared. When using vertical welding, the grains along the wall of the finger-like penetration (FLP) were refined by a more violent flow driven by droplet impingement running in the confined space created by FLP. When using inclined welding, the sharp inflection point disappeared and the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Figure 5 shows the height, width, and forming coefficient of the weld reinforcement It can be seen from the above analysis that the shape of the upper surface of the molten pool is jointly determined by the droplet impact, which plays an active driving role, and the wall constraint, which plays a passive restraining role. When the base metal surface is not completely penetrated, the droplet impact promotes the molten metal to flow in the molten pool [24]. When it flows to the bottom wall of the molten pool, the solid bottom wall restricts a large amount of molten metal to flow backward, thus, forming an upper surface reinforcement in the central plane.…”
Section: Effect Of Driving Forces and Wall Constraint On The Flow Pat...mentioning
confidence: 99%
“…Figure 5 shows the height, width, and forming coefficient of the weld reinforcement It can be seen from the above analysis that the shape of the upper surface of the molten pool is jointly determined by the droplet impact, which plays an active driving role, and the wall constraint, which plays a passive restraining role. When the base metal surface is not completely penetrated, the droplet impact promotes the molten metal to flow in the molten pool [24]. When it flows to the bottom wall of the molten pool, the solid bottom wall restricts a large amount of molten metal to flow backward, thus, forming an upper surface reinforcement in the central plane.…”
Section: Effect Of Driving Forces and Wall Constraint On The Flow Pat...mentioning
confidence: 99%
“…Despite the progress made over the last few decades, many problems remain unsolved. For example, Zhang et al [10] compared the effect of welding direction, namely vertical and inclined configurations, on the weld profile and grain morphology obtained using double pulsed-gas metal arc welding processes.…”
Section: Weldabilitymentioning
confidence: 99%
“…Moreover, the profile of a weld bead is also impacted by the direction of droplet impingement. Zhang et al [11] reported that the center lines of the lower part and the upper portion no longer coincides once the welding torch is inclined. Although the molten behavior has been studied quite adequately by the mentioned researches, all the weld pool walls involved above are almost in their solid state, and the role played by the wall in affecting the flow pattern and the resultant bead profile is rarely reported.…”
Section: Introductionmentioning
confidence: 99%